Long-Lived Plasma Cells Secrete High-Affinity Antibodies Responding to a T-Dependent Immunization in a Teleost Fish - Wu, Liting; Fu, Shengli; Yin, Xiaoxue; Guo, Zheng; Wang, Anli; Ye, Jianmin (Frontiers in Immunology, 2019)
The recent discovery of long-lived plasma cells (LLPCs) in mammals, which provide a constant expression of specific high-affinity antibodies that mediate humoral memory, has caused a dramatic paradigm shift in the study of immunity and vaccine development. In teleost fish, there are few studies regarding the association between LLPCs and antibody production, and the affinity of the antibodies secreted by the LLPCs is poorly understood. In the present study, channel catfish (Ictalurus punctatus) were immunized with trinitrophenylated-keyhole limpet hemocyanin (TNP-KLH) to examine TNP-specific antibody titers, affinities, antibody-secreting cell dynamic changes, and especially the affinity of secreted antibodies by LLPCs post-immunization. We demonstrated that TNP-specific LLPCs were generated starting at week 4 post-immunization, achieved a maximal number at week 8, and maintained a comparable level throughout 18-week post-immunization period, which was correlated with the dynamics of serum antibody titers and affinity maturation in the response. The LLPCs appeared to mostly reside within, or migrate to, the anterior kidney (bone marrow-like tissue in mammals), but a small portion was also located in the spleen and peripheral blood. The antibodies produced by the LLPCs possessed high affinities, indicating that the generation and development of LLPCs were driven by affinity selection in teleosts. Collectively, the results of this study provide insights toward the evolutionary understanding of the affinity-dependent mechanism of LLPC generation and development.